Ethnicity Political Power in East Asia - M. Dahrin La Ode; Adnan Madjid; Ridwan Ridwan (The Republic of Indonesia Defense University, 2016)
The purpose of this study to analyze the strategy of the political power of ethnicity, political objectives ethnicity, and the US response to the political power of ethnicity East Asia (Japan, South Korea and China). This type of qualitative research, data collection techniques interviews, and literature, and data using the analytical techniques and models Miles Hubberman. The findings of this study the map of the political power of ethnicity in East Asia they are all on the Natives. Japan's defense system was originally “Self Defense” to “Collective Self Defence”, South Korea's defense system shifts from “Defense Ambrella” into the system “Extended Nuclear Deterrence”; China shifted from “Continental Defense” to “Opensive Defense”. Political objectives etnisistas East Asia (Japan, South Korea and China) to realize “Bonum Publicum”. US response to the political power of ethnicity in East Asia are routed through the strength of the economic, political, military and East Asia (Japan, South Korea and China), using a system of “persuading, the protection system and pressing system. However, in the light of “persuasion”, “protection” and “pressure” varies between countries. Map of the political power of ethnicity in East Asia “base on power” Yamato indigenous groups, Hangukin, and Chung Hua.